Associations of accelerometer-measured physical activity and sedentary time with renal function and chronic kidney disease: a national population-based study - Suo, Xiangying; Liu, Yanhua; Amoah, Adwoa Nyantakyiwaa; Bo, Yacong; Lyu, Quanjun (Frontiers in Endocrinology, 2024)
There is limited information about the relationship between physical activity and sedentary behaviors in chronic kidney disease (CKD). Therefore, this study aims to explore the associations of accelerometer-measured physical activity and sedentary behaviors with CKD. A cross-sectional study was conducted using data from the National Health and Nutrition Examination Survey in the 2003-2004 and 2005-2006 survey cycles. A uniaxial accelerometer measured physical activity (PA) and sedentary time (ST). The associations of PA and ST with estimated glomerular filtration rate (eGFR) and odds of CKD adopted the generalised linear regression, multivariable logistic regression and isotemporal substitution models. A total of 5,990 adults with 605 CKD patients were included in this study. Compared with the individuals in the first quartile group, participants in the fourth quartile of lowintensity physical activity (LIPA), moderate to vigorous physical activity (MVPA), ST were associated with 52% (35%, 65%), 42% (14%, 62%) lower odds of CKD and 64% (17%, 131%) higher odds of CKD, respectively. Substituting 30min/day of ST with equivalent LIPA/MVPA contributed to risk reduction in CKD. The findings suggest that increased LIPA, MVPA and reduced ST was associated with a lower risk of CKD and that replacing ST with LIPA may decrease the risk of CKD.